COERCION RATES IN DIFFERENT MENTAL HEALTH CARE MODELS: EXPERIENCES FROM RECOVER-E PROJECT SAMPLES IN MONTENEGRO - Dedovic, Jovo; Djurisic, Tatijana; Tomcuk, Aleksandar; Miladinovic, Danijela; Vlahovic, Sandra; Macic, Aleksandar; Roganovic, Vasko; Wijnen, Ben (Engrami, 2022)
In 2018, RECOVER-E project activities were initiated in Montenegro, within the Horizon 2020 program. After conducting a thorough situation analysis of the setting and circumstances of treatment of patients with severe mental illnesses, the community mental health team (CMHT) within the Special Psychiatric Hospital Kotor was established. This team became responsible for the management of treatment of a group of users with severe mental health illnesses, based on the principles of „Flexible Assertive Community Treatment (FACT – A Dutch model). The main objective of this research was to establish whether there were substantial differences regarding the use of coercive measures during the hospital readmissions in the group of patients treated by the CMHT, compared to usual mental health care in Montenegro. Materials and methods: A sample of 202 users of mental health services from Kotor and surrounding municipalities were recruited. Patients were randomized into two similar-sized groups - the intervention group, whose treatment was managed by the multidisciplinary CMHT, and the control group where treatment, as usual, was continued. To estimate and follow up the frequency of application of coercive measures, hospital documentation was used. Mac Arthur Admission Experience Survey has been used after completion of the study to explore the individual levels of perceived coercion during hospital readmissions. Results: Patients in the intervention group had statistically significant less coercive intervention (such are mechanical restraining and forced medication) during the study. There were no other significant differences between the t In 2018, RECOVER-E project activities were initiated in Montenegro, within the Horizon 2020 program. After conducting a thorough situation analysis of the setting and circumstances of treatment of patients with severe mental illnesses, the community mental health team (CMHT) within the Special Psychiatric Hospital Kotor was established. This team became responsible for the management of treatment of a group of users with severe mental health illnesses, based on the principles of „Flexible Assertive Community Treatment (FACT – A Dutch model). The main objective of this research was to establish whether there were substantial differences regarding the use of coercive measures during the hospital readmissions in the group of patients treated by the CMHT, compared to usual mental health care in Montenegro. Materials and methods: A sample of 202 users of mental health services from Kotor and surrounding municipalities were recruited. Patients were randomized into two similar-sized groups - the intervention group, whose treatment was managed by the multidisciplinary CMHT, and the control group where treatment, as usual, was continued. To estimate and follow up the frequency of application of coercive measures, hospital documentation was used. Mac Arthur Admission Experience Survey has been used after completion of the study to explore the individual levels of perceived coercion during hospital readmissions. Results: Patients in the intervention group had statistically significant less coercive intervention (such are mechanical restraining and forced medication) during the study. There were no other significant differences between the two groups regarding the total number of readmissions and number of hospital days. Conclusion: This study showed that CMHT care could reduce some of the coercive measures during the treatment of severe mental illnesses, which can lead to the increased perceived quality of care and better treatment adherence. Keywords: FACT, CMHT, mental, illness, readmission.